1) √(2x-1) <= 8-2x
2) √[(x+1)(4-x)] > x-2
3) √(x-2x^2+1) > 1-x
4) √(x+5) - √(x+4) > √(x+3)
5) √(5x-1) - √(x-1) > √(2x-4)
6) √(x+3) >= √(2x-8) + √(7-x)
7) √(x+2) - √(3-x) < √(5-2x)
8) √(x+1) > 3 - √(x+4)
9) √(5x-1) - √(4x-1)<= 3√x
10) { {√[2(x^2-16)]} / √(x-3) }+ √(x-3) > (7-x) / √(x-3)
Giúp mình 10 câu này với ạaa
1) |2x - 1| = 5
2) |2x - 1| = |x + 5|
3) |3x + 1| = x - 2
4) |3 - 2x| = x + 2
5) |2x - 1| = 5 - x
6) |- 3x| = x - 2
7) |2 - 3x| = 2x + 1
8) |2x - 1| + |4x ^ 2 - 1| = 0
9) (2x + 5)/(x + 3) + 1 = 4/(x ^ 2 + 2x - 3) - (3x - 1)/(1 - x)
10) (x - 1)/(x + 3) - x/(x - 3) = (7x - 3)/(9 - x ^ 2)
11) 5 + 96/(x ^ 2 - 16) = (2x - 1)/(x + 4) + (3x - 1)/(x - 4)
12) (2x)/(2x - 1) + x/(2x + 1) = 1 + 4/((2x - 1)(2x + 1))
13) (x + 2)/(x - 2) - 1/x = 2/(x ^ 2 - 2x)
14) x/(2x - 6) + x/(2x + 2) = (2x + 4)/(x ^ 2 - 2x - 3)
CMR:
\(\left(\frac{X^2-2X}{2X^2-8}-\frac{2X^2}{8-4X+2X^2-3X^3}\right).\left(1-\frac{1}{X}-\frac{2}{X^2}\right)=\frac{X+1}{2X}\)
A=(x ² - 2x/ 2x ² +8 +2x ²/x ³ -2x ² -4x-8) × (1-1/2-2/x ²) a.rút gọn
Tìm điều kiện có nghĩa:
1) \(\sqrt{2x^2}\)
2) \(\sqrt{-x}\)
3) \(\sqrt{-x^2-3}\)
4) \(\sqrt{x^2+2x+3}\)
5) \(\sqrt{-a^2+8a-16}\)
6) \(\sqrt[]{16x^2-25}\)
7) \(\sqrt{4x^2-49}\)
8) \(\sqrt{8-x^2}\)
9) \(\sqrt{x^2-12}\)
10) \(\sqrt{x^2+2x-3}\)
11) \(\sqrt{2x^2+5x+3}\)
12) \(\sqrt{\dfrac{4}{x-1}}\)
13) \(\sqrt{\dfrac{-1}{x-3}}\)
14) \(\sqrt{\dfrac{-3}{x+2}}\)
15) \(\sqrt{\dfrac{1}{2a-1}}\)
16) \(\sqrt{\dfrac{2}{3-2a}}\)
17) \(\sqrt{\dfrac{-1}{2a-5}}\)
18) \(\sqrt{\dfrac{-2}{3-5a}}\)
19) \(\sqrt{\dfrac{-a}{5}}\)
20) \(\dfrac{1}{\sqrt{-3a}}\)
giải pt
a 2(x+3)(x-4)=(2x-1)(x+2)-27
b (3x+2)(x-1)-3(x+1)(x-2)=4
c (x+2)(x^2 -2x+4)-x(x-3)(x+3)=26
d (3x+2)(3x-2)-(3x-4)^2=28
e 5(x+3)^2-5(x-4)(x+8)=3x
f 2x(x+2)^2-8x^2=2(x-2)(x^2+2x+4)
g (2x-1)(4x^2+2x+1)-4x(2x^2-3)=23
h x(x-2)(x+2)-(x-3)(x^2+3x+9)+1=0
i x(x^2+x+1)-(x-1)(x+1)x=x^2+2
giải pt
a 3x(x-1)+2(x-1)=0
b x^2-1-(x+5)(2-x)=0
c 2x^3 +4x^2-x^2+2=0
d x(2x-3)-4x+6=0
e x^3-1=x(x-1)
f (2x-5)^2 -x^2-4x-4=0
h (x-2)(x^2+3x-2)-x^3+8=0
Giải các pt sau:
1)x- căn 2x-5=4
2)căn 2x² - 8x +4=x -2
3)căn x²+ x -12=8- x
4)căn x² - 3x -2= căn x -3
5)căn 2x + 1=2 + căn x - 3
6)căn x +2 căn x-1 -căn x - 2 căn x-1=-2
7) căn x-2 +căn x+3 =5
8) căn x² -4x +3 + x² -4x =-1
Giải các phương trình sau
1. (2x^2-3x+1)(2x^2+5x+1)=9x^2
2. (x+2)(x+3)(x+8)(x+12)=4x^2